2019
DOI: 10.1016/j.electacta.2019.03.203
|View full text |Cite
|
Sign up to set email alerts
|

The role of glycine in the iron-phosphorous alloy electrodeposition

Abstract: The influence of glycine on the iron phosphorous alloy electrodeposition was investigated by electrochemical quartz microbalance (EQMB), in-situ external reflection FTIR spectroscopy, and electrochemical impedance spectroscopy (EIS) measurements. An increase of glycine concentration leads to a decrease of the iron-phosphorous alloy electrodeposition rate and an increase of hydrogen evolution. Strong adsorption of glycine species, such as H 2 (gly) þ , H(gly) ± or/and Fe(gly) þ , have been observed during the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A negative potential scan in the Fe-W and the Fe-W-P baths at pH 3 resulted in a negative current wave at ca. −0.4 V (Figure 1a), which can be interpreted as hydrogen evolution supported by the measured charge density |∆q| [9]. The absence of any frequency change (∆f), i.e., any mass increase, indicates the generation of a gas uncoupled from the surface.…”
Section: Electrochemical Quartz Microbalancementioning
confidence: 66%
See 2 more Smart Citations
“…A negative potential scan in the Fe-W and the Fe-W-P baths at pH 3 resulted in a negative current wave at ca. −0.4 V (Figure 1a), which can be interpreted as hydrogen evolution supported by the measured charge density |∆q| [9]. The absence of any frequency change (∆f), i.e., any mass increase, indicates the generation of a gas uncoupled from the surface.…”
Section: Electrochemical Quartz Microbalancementioning
confidence: 66%
“…It has been shown that the addition of phosphorous can improve the magnetic properties of electrodeposited coatings [7,8]. A detailed study based on electrochemical in-situ techniques led to a mechanistic understanding of the Fe-P alloy electrodeposition [9]. An increase of the P content exerts a beneficial effect on the corrosion resistance [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the deposit is amorphous when the P content is greater than 8 wt.%. To date, numerous researchers have employed single-factor and orthogonal experiments to study the impacts of different amorphous Fe-P electrodeposition process parameters on the behaviours and properties of deposits [10,11,22,23]. However, there is a lack of quantitative studies on the correlations among parameters, P contents and deposit properties.…”
Section: Introductionmentioning
confidence: 99%
“…The peculiarities mentioned above lead to a need for a detailed investigation of targeted alloy deposition even in the case of simple as possible bath composition., e.g., by using controlled hydrodynamic conditions [31,32] or/and complementary electrochemical techniques (quartz crystal microbalance coupled with electrochemical techniques) [33,34].…”
Section: Introductionmentioning
confidence: 99%